Cadaver Study on the Branching Pattern of the Splenic Artery in a Bangladeshi Population - Alim, Abdul; Nurunnabi, Abu Sadat Mohammad; Mahbub, Sabiha; Ahmed, Rukshana; Ara, Shamim (Medicine Today, 2014)
The spleen is the largest single mass of lymphoid tissue in all vertebrates. Arterial blood supply correlates with the functional capability of the human spleen. A cross-sectional, descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008, to see the arterial pattern in the human spleen. 30 human spleens were collected from the unclaimed dead bodies that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (15-29 years), group B (30-49 years) & group C (50-69 years). Then macroscopic dissection was done and radiological angiograph was taken to see the arterial pattern in the human spleen. The splenic artery was the origin of sole blood supply in all the specimens. Two lobar branches were found in 70% of specimens and three branches in 23%. Four lobar branches were evident in only 2 specimens. Moreover, several segmental branches and polar arteries were found in the spleen of different ages. The distance between the splenic artery (before giving its lobar branches) and the hilum of the spleen were found 2.99±0.73 cm, 3.79±1.43 cm and 3.51±1.66 cm in group A, B and C respectively. However, the difference was not statistically significant among the study groups. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21305 Medicine Today 2014 Vol.26(1): 15-17